Deliberative Capacity of Individuals – Dimensions and Determinants - Lundell, Krister (Advances in Social Sciences Research Journal, 2014)
This essay deals with an area of deliberative democracy where research has hitherto been limited: individual deliberative capacity. The main objective of the study is to define and create a concept and a measure of deliberative capacity of individuals; in addition, some determinants of deliberative capacity are examined. The purpose of and the very meaning of deliberative democracy, and what deliberation requires from the citizen constitute the point of departure in developing the dimensions of deliberative capacity. The aim is to capture the cognitive and attitudinal characteristics that are beneficial to deliberation, such as respectful, reciprocal, tolerant, empathic and open-minded; that is, characteristics that largely define a “deliberative citizen”. Three dimensions are elaborated, labeled generalized trust, equality and other-regarding ability. In order to examine the concept empirically, the dimensions are transformed into an index of deliberative capacity by means of survey data from the European Social Survey 2008. The analysis suggests that education is the most important socio-demographic variable; women also have more deliberative capacity than men. Non-institutionalized political participation clearly surpasses electoral and associational activity as a determinant of deliberative capacity. Naturally, political interest enhances capacity, whereas internal efficacy is of modest importance.